1988
DOI: 10.1002/1097-0142(19881115)62:10<2098::aid-cncr2820621005>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant therapy of breast cancer with or without additional treatment with alternate drugs

Abstract: Three hundred ten patients with Stage II or Stage III breast cancer were entered on an adjuvant protocol consisting of a combination of 5-fluorouracil, doxorubicin, cyclophosphamide, vincristine, and prednisone (FACVP). In the second phase of the study, patients with estrogen receptor-negative tumors received sequential courses of methotrexate and vinblastine. Other patients, who were estrogen receptor-positive or unknown, were randomized to receive either tamoxifen alone or tamoxifen plus methotrexate and vin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1992
1992
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Patients who showed a strong positive response with tumor regression (from inoperable to operable size) and were scheduled for surgery were evaluated two weeks after the third cycle of chemotherapy, while patients who showed a slow response or no response received another three cycles of NACT and were evaluated thereafter. 1 H MRS data from normal breast tissues of healthy volunteers (controls, N ϭ 28) were used to compare the data obtained from the LABC patients. Only patients with LABC (i.e., TNM stages IIA, IIIA, IIIB, and IV) were included in this study.…”
Section: Patientsmentioning
confidence: 99%
“…Patients who showed a strong positive response with tumor regression (from inoperable to operable size) and were scheduled for surgery were evaluated two weeks after the third cycle of chemotherapy, while patients who showed a slow response or no response received another three cycles of NACT and were evaluated thereafter. 1 H MRS data from normal breast tissues of healthy volunteers (controls, N ϭ 28) were used to compare the data obtained from the LABC patients. Only patients with LABC (i.e., TNM stages IIA, IIIA, IIIB, and IV) were included in this study.…”
Section: Patientsmentioning
confidence: 99%
“…This assumption was based on a mathematical model as well as on experimental and early clinical observations regarding advanced Hodgkin's disease and small-cell lung cancer (Evans et al, 1987). Our results in patients with one to three positive axillary nodes suggest that six full cycles of CMF in premenopausal or FEC in post-menopausal women are superior to the administration of CMF/EC regimen for both DFS (Spittle et al, 1987;Budzar et al, 1988;Falkson et al, 1991;Bonadonna et al, 1995). Conversely, results from the ECOG (Tormey et al, 1992) showed prolonged DFS in patients receiving alternating chemohormonotherapy in the adjuvant setting, although the use of hormonal manipulation obscures the interpretation of data.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, the overall goal of treatment in this setting is to provide local control and improve overall survival. Today, most patients with locally advanced breast cancer receive neoadjuvant chemotherapy followed by mastectomy, axillary node dissection, and radiation therapy, followed by consolidation chemotherapy depending on tumor response (79–81). Response to neoadjuvant chemotherapy is rated on breast physical examination, and is usually classified as no response (NR), partial response (PR), or complete response (CR) based upon residual tumor on palpation.…”
Section: Evaluation Of the Breast After Neoadjuvant Chemotherapymentioning
confidence: 99%
“…Investigators reported that preoperative neoadjuvant chemotherapy, along with systemic therapy after local treatment by surgery and radiation, improved disease‐free and overall survival (79–81). Preoperative neoadjuvant chemotherapy is defined as combined chemotherapy given to breast cancer patients who have large tumor masses (stage T3 or T4) and/or regional lymph node involvement prior to definitive surgical treatment for local control.…”
Section: Evaluation Of the Breast After Neoadjuvant Chemotherapymentioning
confidence: 99%